Puccini's Turandot - Adami, Giuseppe, 1878-1946.; Fisher, Burton D.; Simoni, Renato, 1875-1952.; Gozzi, Carlo, 1720-1806.; Adami, Giuseppe, 1878-1946.; Adami, Giuseppe, 1878-1946.; Puccini, Giacomo, 1858-1924. (Coral Gables, Fla. : Opera Journeys, 2002)
Turandot, considered by many Puccini's magnum opus, is an incredible operatic masterpiece, a remarkable blend of heroic grandeur, exoticism, and powerful romantic and poignant sentimentalism.
Commentary and analysis -- Principal characters in Turandot -- Brief story synopsis -- Story narrative with music highlights -- Libretto -- Discography -- Videography -- Dictionary of opera and musical terms.
Discography: pages 87-90.
Videography: pages 91-93.
Print version record.
eBooks on EBSCOhost
Keywords: Puccini, Giacomo, -- 1858-1924.; Turandot (Puccini, Giacomo); Operas -- Librettos; Opéras -- Livrets; MUSIC -- Genres & Styles -- Opera; Operas -- Librettos